2020
DOI: 10.1007/978-3-030-45002-1_4
|View full text |Cite|
|
Sign up to set email alerts
|

Toward Employee-Driven Digital Innovation in Public Organizations Through the Use of Action Design Research

Abstract: Innovation is important for development in the private sector, but inevitably public sector also needs innovation to enhance services and processes, with research on employee-driven digital innovation in public organizations being limited. We propose a study in a public organization based on action design research (ADR) methodology to enhance theoretical knowledge and develop practice in relation to employee-driven digital innovation. This research-in-progress study follows the divided stages of ADR, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Their experience of "innovation champions" relates to employees driven by intrinsic motivation (Reibenspiess et al, 2019). Other studies of employee-driven digital innovation in public organizations supports this finding, identifying individuals who constantly had a development focus, either for the organization or services they provided to their users, when performing their daily work tasks (Opland et al, 2021). Creativity thus seems to be linking employee-driven digital innovation and intrinsic motivation.…”
Section: Intrinsic Motivation and Digital Innovationmentioning
confidence: 85%
See 1 more Smart Citation
“…Their experience of "innovation champions" relates to employees driven by intrinsic motivation (Reibenspiess et al, 2019). Other studies of employee-driven digital innovation in public organizations supports this finding, identifying individuals who constantly had a development focus, either for the organization or services they provided to their users, when performing their daily work tasks (Opland et al, 2021). Creativity thus seems to be linking employee-driven digital innovation and intrinsic motivation.…”
Section: Intrinsic Motivation and Digital Innovationmentioning
confidence: 85%
“…However, if we return to the study by Smith et al (2012), we see that managerial support has been highlighted as a variable that influences employeedriven innovation. Previous studies of public organizations, like Opland et al (2021), have shown that this is not only related to local management support, but also to support from senior management.…”
Section: Strategy and Motivationmentioning
confidence: 94%
“…Moreover, some articles assert that EDI significantly influences radical innovation in organizations [3,8]. EDI has also been employed and positively impacted innovativeness in the public sector [62]. However, some literature also underscores the adverse effects of EDI on organizational innovativeness.…”
Section: Meso-level Effectsmentioning
confidence: 99%
“…Employees require some form of guidance and a robust as well as trusted communication channel, for example, through a digital platform, a person, or other opportunities, when undertaking innovative tasks or promoting their ideas to a higher hierarchical level to gain recognition [60]. Therefore, managerial commitment is necessary to further increase participation in EDI [8,30,42,50,62], resulting in greater employee motivation [50,59] and aiding the creation of a communication bridge between managers and employees [6]. For this communication to function properly, knowledge and information need to be distributed bidirectionally [38], which may result in structural changes.…”
Section: Meso-level Effectsmentioning
confidence: 99%
See 1 more Smart Citation